Understanding the role of appraisal in the relationship between work overload, work engagement and burnout in South African organisations - Dzuguda, Hulisani (Organisational Psychology, 2020)
The objective of the study was to investigate how individual appraisal of high workload as a challenge or a hindrance stressor correlates with work engagement and burnout. The work environment is fraught with high workloads, resulting in stress for employees. The cost of employee stress and ill health to organisations and society is reported to be high due to lost productivity and healthcare costs. The current study used the challenge-hindrance stressor model to determine the impact of appraisal on the relationship between work overload and work engagement/burnout. The current study proposed that employees experience both work engagement and burnout concurrently depending on whether they appraise work overload as a challenge or a hindrance stressor. An explanatory quantitative design was used to survey employees from multiple organisations in South Africa, yielding 144 full-time, permanently employed respondents. Findings from the study indicated that stressors that were appraised as challenges were linked to work engagement, whereas stressors that were appraised as hindrances were linked to burnout. The study also found that employees appraise work overload as a hindrance not a challenge, resulting in a negative relationship between work overload and work engagement and a positive relationship between work overload and burnout. The implication is that when employees have high workloads, their engagement does not increase; their likelihood of burnout increases. The study determined no positive outcomes of high workloads, only the risk of highly engaged employees becoming fatigued and burnt out. Hence, it is recommended that organisations manage the workloads of their employees.